6x+3(x+3)=72

Simple and best practice solution for 6x+3(x+3)=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3(x+3)=72 equation:


Simplifying
6x + 3(x + 3) = 72

Reorder the terms:
6x + 3(3 + x) = 72
6x + (3 * 3 + x * 3) = 72
6x + (9 + 3x) = 72

Reorder the terms:
9 + 6x + 3x = 72

Combine like terms: 6x + 3x = 9x
9 + 9x = 72

Solving
9 + 9x = 72

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 9x = 72 + -9

Combine like terms: 9 + -9 = 0
0 + 9x = 72 + -9
9x = 72 + -9

Combine like terms: 72 + -9 = 63
9x = 63

Divide each side by '9'.
x = 7

Simplifying
x = 7

See similar equations:

| -2x+5x=0 | | 3x+2(5x+9)1=135 | | tn=-1 | | 3-6x=5x+113 | | 4(4x-3)+6=-3 | | 3x+2(5x+9)1=35 | | -7=5+3a-6a | | 72x^4-50x^2=0 | | -18=-2n-4n | | 10x+-3=4x-21 | | 11x-3(6-3x)= | | 3x+4(3x-5)=130 | | 3.98i+11.94=23.88 | | 3x+15=2x-5 | | 8-(6-7)=0 | | 8(x+4)=-64 | | 3y+2y=2y-5x | | X+m=no+rq | | 7x-32-9x=8 | | Y=3x^5+3x^3-60x | | -6-(6-6p)=0 | | 4(4-4x)+4=-2x+2-14x | | 5-9+x=65 | | -4=4(3-b) | | 6x+3(4x+2)=96 | | -4x+6=6x+16 | | 9x-1=2x-12 | | -14=3x+10 | | 3x*-5=4x*-2 | | 10+x-6=2 | | 3h-6=24 | | 6i-4=2i+24 |

Equations solver categories